The Protection of the Right to Life at the Intersection between Reproductive Rights and Scientific Progress in the Jurisprudence of the Inter-American Court of Human Rights and the European Court of Human Rights - Fanni, Simona (Araucaria, 2024)
The definition of the beginning of life and the protection of the right to life when conflicting entitlements and interests emerge are highly disputed issues worldwide, and the Inter-American Court of Human Rights (IACtHR) and the European Court of Human Rights (ECtHR) have been called to tackle these questions in their jurisprudence, especially when reproductive rights were at stake. In this respect, this paper focuses on the status of human embryo and on prenatal life and provides an assessment of the approaches that the two Courts have developed when dealing with such delicate issues as in vitro fertilization (IVF) and abortion, respectively through the pervasive scrutiny of the San José Court and its purposeful impact on the domestic sphere and usually through the recognition of a wide margin of appreciation by the Strasbourg Court. In this regard, this paper provides an analysis of the Courts’ most significant case law, as Artavia Murillo v. Costa Rica and ’Beatriz’ cases, with reference to the IACtHR, and the ECtHR’s decisions Vo v. France, Evans v. the United Kingdom, S.H. and Others v. Austria, Costa and Pavan v. Italy, Parrillo v. Italy and A, B, C v. Ireland, while considering the peculiarities of the systems of the American Convention on Human Rights and the European Convention on Human Rights and the role of the Convention on Human Rights and Biomedicine and its Protocols in Strasbourg jurisprudence. Moving from this assessment, this paper aims to suggest possible solutions to improve the results achieved by the two Courts, also through judicial cross-fertilization and through reference to the relevant international instruments according to Article 31(3)(c) of the Vienna Convention on the Law of the Treaties, for example the right to enjoy the benefits of scientific progress enshrined in the International Covenant on Economic, Social and Cultural Rights.